Factors affecting the decision-making process when choosing an event destination: A comparative approach between Vilamoura (Portugal) and Marbella (Spain) - Houdement, Julie; C. Santos, José António; Serra, Francisco (Journal of Tourism, Sustainability and Well-being, 2017)
Business travel is nowadays a key component of tourism industry and an important instrument for reducing seasonality. Literature has identified several attributes that affect the decision-making process when choosing a destination to hold an event. The main objective of this research is to determine their importance and how they influence the decision-making process. Vilamoura in Portugal and Marbella in Spain are the destinations under analysis, as they are important seaside destinations where business travel has contributed to a successful meeting industry. In order to achieve the study’s aim, a qualitative methodology based on semi-structured interviews both to event organisers and suppliers has been conducted. The findings confirm the hypothesis that underpinned the study, demonstrating that destination image is the main determining site-selection factor. This investigation, proposed as an exploratory examination for further research, could constitute a useful resource for event professionals to improve their destination promotion and their positioning.